Rabbinic narrative : Volume two, Forms, types, and distribution of narratives in Sifra, Sifré to Numbers, and Sifré to Deuteronomy. - Neusner, J. (BRILL, 2003)
Each Rabbinic document, from the Mishnah through to the Bavli, defines itself by a unique combination of indicative traits of rhetoric, topic and particular logic that governs its coherent discourse. But narratives in the same canonical compilations do not conform to the documentary indicators that govern in these compilations, respectively. They form an anomaly for the documentary reading of the rabbinic canon of the formative age. To remove that anomaly, this project classifies the types and forms of narratives and shows that particular documents exhibit distinctive preferences among those ty.